PENGARUH MODAL DAN TENAGA KERJA PER JENIS INVESTASI TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN SLEMAN PASCA OTONOMI DAERAH, TAHUN 2001-2005 - Rudy Badrudin (Fakultas Bisnis Universitas Kristen Duta Wacana, 2011)
ABSTRACT This research analyze the effect of capital and labor of Foreign Investment, Local Investment, and Non-facility Investment on Gross Domestic Regional Product in Sleman Regency after regional autonomy. Based on research method using 3 models of regression equation with significance level of 5%, the result are capital and labor of Foreign Investment had no significant effect on Gross Domestic Regional Product in Sleman Regency; capital of Local Investment had no significant effect on Gross Domestic Regional Product in Sleman Regency and labor of Local Investment had significant effect on Gross Domestic Regional Product in Sleman Regency, capital and labor of Non-facility Investment had no significant effect on Gross Domestic Regional Product in Sleman Regency. Keywords: capital, labor, foreign invesment, local invesment, non-facility invesment